HEAVY METALS CONCENTRATION IN SEDIMENT OF LLUTA RIVER BASIN - Copaja, S. V.; Muñoz, F. J. (Journal of the Chilean Chemical Society, 2018)
Northern Chile is characterized by water scarcity. The Lluta River, located in the XV region of Arica and Parinacota, is the one of the main rivers in northern Chile. The elevated levels of metals and metaloids in the river reduce the agricultural productivity and variety of species can be cultivated within the valley, which are of great importance for the consumption of the inhabitants of the area. Heavy metals in river bottoms may cause various effects on the water quality, as such the capacity to accumulate metals; levels of toxicity and metal stabilization in sediments have often been considered a pollution index of a territory. In this work the concentrations of Al, Cu, Fe, Mn, Mo, Pb and Zn from the pseudo-total and labile fraction of Lluta river sediments were studied. Samples from 10 sites along the river were collected. The sediments were characterized determining: pH, electrical conductivity, organic carbon (OC), organic total carbon (OTC), available phosphorus and boron. Heavy metals were analyzed by Atomic Absorption Spectroscopy (AAS). For the metals analyzed in the pseudo-total fraction, the highest concentrations found were: Al in the site 10, (17061 mg kg-1) and Fe on site 6, (29898 mg kg-1). For the labile fraction, highest concentrations of metals were: Al in site 6 (1079 mg kg-1), Fe in site 9, (275 mg kg -1) and Mn in site 9 (1578 mg kg-1). Using the Risk assessment code (RAC), the site 6 presents the greatest risk with high values of Cu, Mn, Pb and Zn, followed by site 1 with high values of Mn, Cu and Zn, and site 9 with high values of Mn, Cu and Pb. On the other hand, the MacDonald PEC (probable effect concentration) and TEC (threshold effect concentration) toxicity criteria, showed that the sites 4 and 6 have levels above the TEC for Cu, Fe, Pb and Zn, and levels above the PEC at six sites for Mn.